From ADR to ODR: Can technology shape the future of mediation practice? - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2012)
Imagine an e-mediator who can reframe parties’ feelings and overall mood based on their speech patterns as they talk into an ODR program. Imagine recreating the real-life intensity of emotional and social connections through an avatar in an online mediation setting. Imagine anonymous brainstorming, secret meetings in e-rooms and having access to a web-based intelligent agent to advise parties on walkaway alternatives and interest-based trade-offs. No, this is not a science-fiction film—it is ODR technology, the mediation world biggest kept secret.